Quantitative gastrointestinal function and corresponding symptom profiles in autonomic neuropathy - Langford, Jordan S.; Tokita, Eric; Martindale, Cecilia; Millsap, Leah; Hemp, James; Pace, Laura A.; Cortez, Melissa M. (Frontiers in Neurology, 2022)
Purpose Peripheral neuropathies with autonomic nervous system involvement are a recognized cause of gastrointestinal dysmotility for a wide spectrum of diseases. Recent advances in wireless motility capsule testing allow improved sampling of regional and whole gut motility to aid in the diagnosis of gastrointestinal motility disorders and may provide additional insight into segment-specific enteric involvement of peripheral neuropathies affecting autonomic nervous system function. Methods We utilized standardized autonomic nervous system (ANS) reflex assessment and wireless motility capsule testing to evaluate 20 individuals with idiopathic autonomic neuropathy and unexplained gastrointestinal symptoms. Additionally, we examined the relationship between quantifiable autonomic neuropathy and gastrointestinal dysmotility at specific neuroanatomical levels. Symptom profiles were evaluated using the 31-item Composite Autonomic Symptom Score questionnaire (COMPASS-31) and compared to wireless motility capsule data. Results We found that transit times were predominately abnormal (delayed) in the foregut (10 of 20; 50%), while contractility abnormalities were far more prominent in the hindgut (17 of 20; 85%), and that motility and symptom patterns, as assessed by the COMPASS-31 GI domain items, generally corresponded. Finally, we also found that there was neuroanatomical overlap in the presence of autonomic reflex abnormalities and WMC-based transit and/or contractility abnormalities. Conclusions We found that transit times were predominately abnormal in the foregut and midgut, while contractility abnormalities were far more prominent in the hindgut in individuals with idiopathic autonomic neuropathy. There was a high rate of agreement in segmental wireless motility capsule data with neuroanatomically corresponding standardized ANS function measures (e.g., cardiovagal, sudomotor, adrenergic). Expanded sudomotor testing, including additional neuroanatomical segments, could provide additional indirect assessment of visceral involvement in ANS dysfunction.